ISLAM AND LOCAL CULTURE IN INDONESIA - Hermansyah Hermansyah (Al-Albab, 2014)
Muslims believe that their religion is universal, suitable to all places and time. Consequently, in practice, Islam can be adapted to various situations and conditions. Therefore, the diversity in Islam is inevitable. Diversity is especially related to aspects of interpretation and religious branches, not things that are principle. This article is about the relationship between Islam and local culture. As recognized by many experts, Islam in Indonesia was spread by peaceful means. Local elements were used in the process of Islamization. As a result, Islam could be accepted by most of society of Indonesia. Islam expressed here shows a distinctive face. Islam can live hand in hand with local culture, especially the culture that is not incompatible with Islam. Keywords: Islam, Islamization, local culture, diversity.